The effectiveness of the active learning strategy in the workshops during kids athletics practice to improve the elements of physical performance and digital success in the relay race (4 x 60 m)in English - bensikaddour, habib; bengueneb, abdarahmane; ahmedbenklaouz, touati; esselma, noria (sports creativity, 2025)
The study aims to know the effectiveness of the use of the active learning strategy in the workshops In the practice of kids' athletics to improve the elements of physical and digital performance in the relay race activity (4 x 60 m) for pupils (11-12) years old. the research sample consisted of 30 students, divided into two control and experimental groups, each (15 boys) having been randomly selected. A set of tests was applied to measure the physical variable of this research, And the research team concluded that the use of the active learning strategy in the workshops In the practice of kids' athletics contributed in a vital and effective way to the improvement of the elements of physical and digital performance in the race of relay.Unlike the traditional teaching methodology based on the fatigue of the learner with unnecessary orders and prohibitions, his result was weak and not significant.